The Learning Management Through the Direct Instruction Model to Improve Vocal Music Skills for Secondary 5 (Grade 11）Students - zhang, Limin; Jermtaisong, Rossarin; Lert-o-pas, Puripun (Journal of Roi Kaensarn Academi, 2023)
The objectives of this research were to: 1) compare the vocal music skills of Secondary 5 (Grade 11) students before and after learning management through the traditional method, 2) compare the vocal music skills of students before and after learning management through direct instruction model, and 3) compare the vocal music skills of students between those studying through the traditional method and those studying through the direct instruction model. The research sample was 30 Secondary 5 (Grade 11) students, selected by cluster random sampling, of Beijing Modern Music School, Beijing, China, in the academic year 2023. The research instruments consisted of: 1) a learning management plan using the traditional method, 2) a learning management plan using the direct instruction model, and 3) an assessment form of vocal music skills. The statistics used for data analysis were mean, standard deviation, independent samples t-test, and dependent samples t-test. The research results showed that: 1) the vocal music skills of Secondary 5 (Grade 11) after studying through the traditional method were higher than before at the statistical significance level of .05, 2) the vocal music skills of students after studying through the direct instruction model were higher than the before at the statistical significance level of .05., and 3) the vocal music skills of students studying through direct instruction model were higher than those studying through the traditional method at the statistical significance level of .05.